Comparative Metabolomic Profiling of Compatible and Incompatible Interactions Between Potato and Phytophthora infestans - Zhu, Jingyu; Tang, Xue; Sun, Yining; Li, Yan; Wang, Yajie; Jiang, Yusong; Shao, Huanhuan; Yong, Bin; Li, Honghao; Tao, Xiang (Frontiers in Microbiology, 2022)
Late blight is one of the main biological stresses limiting the potato yield; however, the biochemical mechanisms underlying the infection process of Phytophthora infestans remains unrevealed. In this study, late blight-resistant potato cultivar Ziyun No.1 (R) and the susceptible cultivar Favorita (S) were inoculated with P. infestans. Untargeted metabolomics was used to study the changes of metabolites in the compatible and incompatible interactions of the two cultivars and the pathogen at 0, 48 and 96 hpi. A total of 819 metabolites were identified, and the metabolic differences mainly emerged after 48 hpi. There were 198 and 115 differentially expressed metabolites (DEMs) in the compatible and incompatible interactions. These included 147 and 100 up-regulated metabolites during the compatible and incompatible interactions, respectively. Among them, 73 metabolites were identified as the P. infestans responsive DEMs. Furthermore, the comparisons between the two cultivars identified 57 resistance-related metabolites. Resistant potato cultivar had higher levels of salicylic acid and several upstream phenylpropanoid biosynthesis metabolites, triterpenoids, and hydroxycinnamic acids and their derivatives, such as sakuranetin, ferulic acid, ganoderic acid Mi, lucidenic acid D2, caffeoylmalic acid, and et al. These metabolites play crucial roles in cell wall thickening and have antibacterial and antifungal activities. This study reports the time course metabolomic responses of potatoes to P. infestans. The findings reveal the responses involved in the compatible and incompatible interactions of potatoes and P. infestans.